A comparative analysis review of plant fibres in advanced bio-based material for sustainable drone construction - Shahar, Farah Syazwani; Hameed Sultan, Mohamed Thariq (Universiti Putra Malaysia Press, 2024)
As researchers’ awareness of ecological impact and climate change increases, several solutions were proposed to help reduce carbon emissions and promote the circularity of materials. Drones technology can help monitor the environment since it can cover a large area, collect real-time images and data, and operate in dangerous environments. Also, the drone’s ecological factor could be further increased by its construction itself. Thus, many researchers are trying to develop a sustainable drone using plant fibres to reduce carbon emissions and ensure the circularity of materials. This review mainly compares the drones made from plant fibres and traditional materials such as plastics and synthetic fibres. This review also includes the introduction of material circularity, the drone’s role in helping ensure material circularity and environment safety, and the advantages and disadvantages of the drone materials. The review will also compare the drone performances made from different bio-based materials with conventional ones. Plant fibres’ role in drone construction significantly contributes to reducing carbon emissions and ensuring the circularity of materials. With drone construction paving the way for other critical structural applications, there is a possibility that plant fibres will soon become the most significant raw material for sustainable products.